Cation-modified diutan gum with excellent dispersion stability

By cationically modifying the Dayi Tan Gum and introducing a specific amount of tetravalent nitrogen groups, the problem that traditional polysaccharides are difficult to stabilize disperse solids and emulsified particles in liquid compositions, achieving better dispersion stability and emulsification stability.

JP7657776B2Active Publication Date: 2025-04-07MP GOKYO FOOD & CHEM CO LTD
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
JP2022510574
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-25
Filing Date
2021-03-24
Publication Date
2025-04-07
Estimated Expiration
2041-03-24

AI Technical Summary

Technical Problem

It is difficult for traditional polysaccharides to disperse solid and emulsified particles stably and uniformly in liquid compositions, resulting in particles being easily raised or deposited and emulsified phase separation.

Method used

The dispersion stability of the liquid composition is improved by cationically modifying Daiyutan gum to introduce 0.3 to 0.8 mg of tetravalent nitrogen groups of valeric acid per gram.

Benefits of technology

The modified cationically modified Dayi Tan Gum significantly improves the uniform dispersion and stability of solid particles and emulsified particles in the liquid composition, reduces the floating or deposition of particles, and improves emulsification stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657776000017
    Figure 0007657776000017
  • Figure 0007657776000001
    Figure 0007657776000001
  • Figure 0007657776000002
    Figure 0007657776000002
Patent Text Reader

Abstract

This cation-modified diutan gum is has a configuration in which a portion of hydroxyl groups are substituted by quaternary nitrogen-containing groups represented by chemical formula (1), wherein the cation charge derived from the quaternary nitrogen-containing groups is 0.3 to 0.8 meq / g.
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims priority to Japanese Patent Application No. 2020-054131, the entire disclosure of which is incorporated herein by reference. [Technical field]

[0002] The present invention relates to polysaccharides, and more particularly to cationically modified diutan gum. [Background technology]

[0003] Polysaccharides have been used to improve the quality of various products such as food, cosmetics, industrial products, etc. Examples of such polysaccharides include natural polysaccharides such as xanthan gum, tamarind gum, and fenugreek gum.

[0004] Patent Documents 1 to 4 propose cationically modified polysaccharides in which some of the hydroxyl groups are replaced with quaternary nitrogen-containing groups in order to improve the functionality of the polysaccharides. They also state that when the cationically modified polysaccharides are contained in shampoos and the like, the conditioning properties are improved, such as suppressing squeaking during washing of hair.

[0005] In addition, in the liquid composition containing insoluble solid particles, polysaccharides may be used to make the solid particles uniformly dispersed in the liquid composition.For example, in the case of a cosmetic composition, polysaccharides may be used to make the scrubbing agent as the solid particles uniformly dispersed in the cosmetic composition.Furthermore, when the liquid composition is an emulsion composition, polysaccharides may be used to make the emulsion particles uniformly dispersed in the composition. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japan Special Publication No. 47-20635 [Patent Document 2] Japanese Patent No. 4716110 [Patent Document 3] Japanese Patent Publication No. 2007-63446 [Patent Document 4] Japanese Patent Publication No. 2012-1676 Summary of the Invention [Problem to be solved by the invention]

[0007] However, when using conventional polysaccharides, it may be difficult to stably and uniformly disperse the solid particles or emulsified particles in the liquid composition, for example, the solid particles may float to the liquid surface or precipitate. Furthermore, when the liquid composition is an emulsion composition, phase separation may occur between the oil component and water, and emulsion particles may not be uniformly dispersed. Therefore, there is a continuing demand for polysaccharides that can improve the dispersion stability of the liquid composition.

[0008] Under these circumstances, the present inventors conducted intensive research and found that cation-modified diutan gum, obtained by cationically modifying a polysaccharide called diutan gum, improves the dispersion stability of the liquid composition when the cation-modified diutan gum is adjusted to a specific cationic charge amount.

[0009] That is, an object of the present invention is to provide a cation-modified diutan gum that has excellent properties in improving the dispersion stability of a liquid composition. [Means for solving the problem]

[0010] The cation-modified diutan gum according to the present invention is A cation-modified diutan gum in which a portion of the hydroxyl groups is substituted with a quaternary nitrogen-containing group represented by chemical formula (1), The amount of cationic charge derived from the quaternary nitrogen-containing group is 0.3 to 0.8 meq / g. [ka] (R in the formula 1 and R 2 is an alkyl group having 1 to 3 carbon atoms, and R 3 is an alkyl group having 1 to 24 carbon atoms, and R 4 and R 5 is an alkyl group having 1 to 3 carbon atoms or a hydrogen atom, and X - indicates a monovalent anion)

[0011] The cationically modified diutan gum according to the present invention preferably comprises: R 4 and R 5 is a hydrogen atom.

[0012] The cationically modified diutan gum according to the present invention preferably comprises: R 3 is an alkyl group having 1 to 3 carbon atoms.

[0013] The cationically modified diutan gum according to the present invention preferably comprises: R 1 , R 2 and R 3 is a methyl group.

[0014] The dispersion stabilizer according to the present invention contains the above cation-modified diutan gum.

[0015] The cosmetic composition according to the present invention contains the above cation-modified diutan gum. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 compares the IR spectra of the cationically modified diutan gum of Example 2 (solid line) and the unmodified diutan gum of Comparative Example 3 (dashed line). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The cation-modified diutan gum according to one embodiment will be described below.

[0018] In order to exert its function, the cation-modified diutan gum of this embodiment is preferably used by being contained in a liquid composition. The liquid composition is composed of a dispersion liquid in which solid particles are dispersed, and contains the cation-modified diutan gum dissolved in the dispersion medium of the dispersion liquid. By containing the cation-modified diutan gum in the liquid composition, the solid particles can be stably and uniformly dispersed in the liquid composition. The dispersion medium may be an emulsion containing an oil component and water. In other words, the liquid composition may be an emulsion composition. In this case, the liquid composition contains the cation-modified diutan gum, so that the emulsion particles contained therein become minute and are stably and uniformly dispersed. In this specification, the degree to which the solid particles and / or the emulsified particles are uniformly and stably dispersed in the liquid composition may be referred to as dispersion stability.

[0019] When the cation-modified diutan gum is contained in the liquid composition containing the solid particles, it is preferable that the aqueous solution containing the cation-modified diutan gum has a specific viscosity. Specifically, the viscosity of an aqueous solution containing the cation-modified diutan gum at a concentration of 0.25% by mass (at 25° C.) is -1 The viscosity is preferably 10,000 to 100,000 mPa·s, and more preferably 30,000 to 60,000 mPa·s, which allows the solid particles to be uniformly dispersed in the liquid composition. The viscosity is a value measured by the method described in the examples.

[0020] When the liquid composition is an emulsion composition, the emulsion composition may be of the oil-in-water (O / W) type or the water-in-oil (W / O) type. The emulsion particle size (median size) is preferably 50 μm or less, and more preferably 40 μm or less, which can improve the emulsion stability of the emulsion composition. The emulsion particle size refers to a value measured by the measurement method described in the Examples.

[0021] The cation-modified diutan gum according to this embodiment is a cation-modified diutan gum in which some of the hydroxyl groups contained in the diutan gum are substituted with a quaternary nitrogen-containing group represented by chemical formula (1). This gives the cation-modified diutan gum a cationic charge. [ka]

[0022] The diutan gum is a polysaccharide that accumulates outside the cells of the genus Alcaligenes during the fermentation process. The repeating units of the diutan gum have a main chain composed of glucose, glucuronic acid, glucose, and rhamnose, and a side chain composed of rhamnose disaccharide. In other words, the diutan gum is an anionic polysaccharide having repeating units of these hexasaccharides. As the diutan gum, a commercially available product can be used. For example, KELCO-VIS DG (manufactured by CP Kelco US, Inc.) and the like can be mentioned.

[0023] In the above chemical formula (1), R 1 and R 2 R represents an alkyl group having 1 to 3 carbon atoms. 1 and R 2 Examples of R include a methyl group, an ethyl group, and a propyl group, and among these, a methyl group is preferable. 1 and R 2 are preferably the same type of functional group. The propyl group may be either an n-propyl group or an iso-propyl group.

[0024] Also, R 3 R represents an alkyl group having 1 to 24 carbon atoms. 3Examples of R include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, and decyl groups. Among these, methyl and ethyl groups are preferred, and methyl groups are more preferred. 3 is R 1 and R 2 It is preferable that the alkyl group is the same type of functional group as that shown in the formula (1). Note that these alkyl groups may be linear, branched, or cyclic.

[0025] Also, R 4 and R 5 represents an alkyl group having 1 to 3 carbon atoms or a hydrogen atom. 4 and R 5 Examples of R include a methyl group, an ethyl group, and a propyl group. 4 and R 5 is preferably a methyl group or a hydrogen atom, more preferably a hydrogen atom. The propyl group may be either an n-propyl group or an iso-propyl group.

[0026] Also, X - X denotes a monovalent anion. - Examples of the cation ion include halide ions such as chloride ion, bromide ion, and iodide ion, methyl sulfate ion, ethyl sulfate ion, etc. Among these, halide ions are preferred, and chloride ions are more preferred.

[0027] The cation-modified diutan gum is synthesized by reacting the diutan gum with a glycidyl trialkyl ammonium salt or a 3-halogeno-2-hydroxypropyl trialkyl ammonium salt having a corresponding structure. In this case, the reaction is carried out in a suitable solvent, preferably an aqueous alcohol, in the presence of an alkali. The introduction of such a quaternary nitrogen-containing group can be carried out according to a conventionally known method, but is not necessarily limited to these.

[0028] It is important that the cationic charge amount of the cation-modified diutan gum is 0.3 to 0.8 meq / g, preferably 0.30 to 0.85 meq / g, more preferably 0.44 to 0.7 meq / g, and even more preferably 0.44 to 0.62 meq / g. When the cationic charge amount is within the above numerical range, the dispersion stability of the liquid composition becomes excellent. In addition, the spinnability of the liquid composition is reduced, and the workability when filling the liquid composition into a container or the like is improved.

[0029] The cationic charge amount means the number of equivalents of the nitrogen content derived from the quaternary nitrogen-containing group contained in 1 g of the cation-modified diutan gum. In other words, the cationic charge amount means a value calculated by the following formula (1). The nitrogen content derived from the quaternary nitrogen-containing group in formula (1) means a value measured by the Kjeldahl method (old cosmetic raw materials standard, general test method, nitrogen determination method, method 2). Since the diutan gum usually contains nitrogen derived from proteins, it is necessary to remove the nitrogen derived from proteins when measuring the nitrogen content of the cationically modified diutan gum. That is, the nitrogen content derived from the quaternary nitrogen-containing group in the cationically modified diutan gum measured by the Kjeldahl method is calculated by subtracting the measured value of the nitrogen content of the diutan gum before cation modification from the measured value of the nitrogen content of the diutan gum after cation modification. This will be specifically explained using the measurement examples of Example 2 and Comparative Example 3 shown in Table 1. The measured nitrogen content of the cation-modified diutan gum (Example 2) was 1.66%, and the measured nitrogen content of the diutan gum before cation modification (Comparative Example 3) was 0.88%, so by substituting these measured values ​​into the following formula (1), the cationic charge amount of the cation-modified diutan gum of Example 2 is calculated to be 0.557 (meq / g).

number

[0030] In addition to the difference in cationic charge, the cation-modified diutan gum of the present embodiment exhibits an IR spectrum different from that of the diutan gum (FIG. 1). Specifically, the IR spectrum of the cation-modified diutan gum shows a decrease in peak intensity (peak height) for some peaks compared to the IR spectrum of the diutan gum. In particular, the 1730 cm -1 A significant decrease in the peak intensity is observed in the first peak P1 near the 1600 cm -1 No significant decrease in peak intensity is observed in the nearby second peak P2. That is, the cationically modified diutan gum has a ratio of the peak intensity of the first peak P1 to the peak intensity of the second peak P2 in the IR spectrum of 0.1 to 0.4. In contrast, the diutan gum has a ratio of the peak intensity of the first peak P1 to the peak intensity of the second peak P2 in the IR spectrum of 0.5 to 1.0. Thus, the cationically modified diutan gum has a smaller ratio than the diutan gum. The IR spectrum is measured by the method described in the Examples, and the peak intensity ratio refers to a value calculated by the method described in the Examples.

[0031] The cation-modified diutan gum of the present embodiment can be used as a dispersion stabilizer for imparting excellent dispersion stability to the liquid composition as described above. The dispersion stabilizer can be suitably used in products such as foods, cosmetics, and industrial products that contain the solid particles and / or the emulsion particles.

[0032] The dosage form of the dispersion stabilizer is not particularly limited, and may be a solid such as a powder or granules, or a liquid such as an aqueous solution. When the dispersion stabilizer is a solid, the content of the cation-modified diutan gum relative to the total mass of the dispersion stabilizer is usually 0.1 to 100% by mass. When the dispersion stabilizer is a liquid, the concentration of the cation-modified diutan gum in the dispersion stabilizer is usually 0.1 to 10% by mass.

[0033] The dispersion stabilizer may contain additives other than the cation-modified diutan gum as long as they can function as such. Examples of the additives include thickeners such as xanthan gum and locust bean gum, lubricants such as magnesium stearate, metal salts such as sodium chloride and potassium chloride, and dispersants (viscosity adjusters) such as glucose and dextrin.

[0034] The liquid composition is preferably a cosmetic composition containing the cation-modified diutan gum. The formulation of the cosmetic composition is not particularly limited, and any formulation can be adopted. Specific formulations include lotion, milky lotion, beauty essence, gel, cream, facial cleanser, oil-in-lotion, sunscreen, shampoo, treatment, body soap, and the like. Among these applications, the cosmetic composition is preferably used in cleansing agents such as facial cleanser, shampoo, and body soap. In other words, the cosmetic composition is preferably a cleansing cosmetic composition used in facial cleanser, shampoo, body soap, and the like.

[0035] The content of the cation-modified diutan gum relative to the total mass of the cosmetic composition is usually 0.05 to 5 mass%, and more preferably 0.1 to 3 mass%, which gives the cosmetic composition excellent dispersion stability, suppresses slimy and sticky feelings during use, and provides a good feel when used.

[0036] The density of the liquid component contained in the cosmetic composition is usually 0.70 to 1.30 (g / mL).

[0037] The oily component that can be contained in the cosmetic composition is preferably an oily component that is easily compatible with hair, skin, nails, etc. Examples of such oily components include fatty acids, fatty acid esters, hydrocarbon oils, and silicone oils.

[0038] The fatty acid is preferably a fatty acid having 8 to 22 carbon atoms, more preferably a fatty acid having 12 to 18 carbon atoms, and even more preferably a fatty acid having 16 to 18 carbon atoms. Examples of the fatty acid having such a carbon number include caprylic acid (8 carbon atoms), undecylenic acid (11 carbon atoms), capric acid (10 carbon atoms), lauric acid (12 carbon atoms), myristic acid (14 carbon atoms), palmitic acid (16 carbon atoms), stearic acid (18 carbon atoms), linoleic acid (18 carbon atoms), linolenic acid (18 carbon atoms), isostearic acid (18 carbon atoms), oleic acid (18 carbon atoms), eicosapentaenoic acid (20 carbon atoms), behenic acid (22 carbon atoms), and docosahexaenoic acid (22 carbon atoms).

[0039] The fatty acid ester is preferably a fatty acid ester having 12 to 54 carbon atoms, more preferably a fatty acid ester having 14 to 50 carbon atoms, and even more preferably a fatty acid ester having 16 to 46 carbon atoms. Examples of the fatty acid ester having such a carbon number include cetyl octanoate (carbon number 24), ethyl laurate (carbon number 14), hexyl laurate (carbon number 18), isopropyl myristate (carbon number 17), octyldodecyl myristate (carbon number 34), myristyl myristate (carbon number 28), 2-hexyldecyl myristate (carbon number 30), glycerin trimyristate (carbon number 45), isopropyl palmitate (carbon number 19), palmitate (carbon number 20), and glyceryl trimethacrylate (carbon number 21). 2-Ethylhexyl palmitate (carbon number 24), 2-heptylundecyl palmitate (carbon number 36), 2-hexyldecyl palmitate (carbon number 34), butyl stearate (carbon number 22), isocetyl stearate (carbon number 34), isocetyl isostearate (carbon number 34), cholesteryl 12-hydroxystearate (carbon number 45), trimethylolpropane triisostearate (carbon number 54), decyl oleate (carbon number 2 8), cetyl lactate (carbon number 19), myristyl lactate (carbon number 17), cetyl 2-ethylhexanoate (carbon number 24), di-2-ethylhexyl ethylene glycol (carbon number 22), tri-2-ethylhexyl trimethylolpropane (carbon number 30), tri-2-ethylhexyl glycerin (carbon number 27), tetra-2-ethylhexyl pentaerythritol (carbon number 37), cetyl 2-ethylhexanoate (carbon number 24), adipine diisobutyl acetate (carbon number 14), 2-heptylundecyl adipate (carbon number 42), 2-hexyldecyl adipate (carbon number 38), neopentyl glycol dicaprate (carbon number 25), diisostearyl malate (carbon number 40), di-2-ethylhexyl sebacate (carbon number 26), diisopropyl sebacate (carbon number 16), 2-ethylhexyl succinate (carbon number 20), and triethyl citrate (carbon number 12).

[0040] The oily component containing a plurality of fatty acids and / or fatty acid esters may be a natural oily component, such as olive oil, jojoba oil, castor oil, mink oil, tall oil, coconut oil, or palm oil.

[0041] Examples of the hydrocarbon oil include liquid paraffin, squalane, α-olefin oligomer, and petrolatum.

[0042] Examples of the silicone oil include linear or branched organopolysiloxanes having low to high viscosity, such as dimethylpolysiloxane, tristrimethylsiloxymethylsilane, caprylyl methicone, phenyl trimethicone, tetraquistrimethylsiloxysilane, methylphenylpolysiloxane, methylhexylpolysiloxane, methylhydrogenpolysiloxane, and dimethylsiloxane-methylphenylsiloxane copolymers, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, dodecamethylcyclohexasiloxane, tetramethyltetrahydrogencyclotetrasiloxane, and tetramethyltetraphenylcyclotetrasiloxane. Examples of such silicone rubbers include cyclic organopolysiloxanes such as tetrasiloxane, amino-modified organopolysiloxanes, pyrrolidone-modified organopolysiloxanes, pyrrolidone carboxylic acid-modified organopolysiloxanes, gum-like dimethylpolysiloxanes with a high degree of polymerization, gum-like amino-modified organopolysiloxanes, and gum-like dimethylsiloxane-methylphenylsiloxane copolymers, as well as cyclic organopolysiloxane solutions of silicone gums and rubbers, higher alkoxy-modified silicones such as stearoxysilicone, higher fatty acid-modified silicones, alkyl-modified silicones, long-chain alkyl-modified silicones, amino acid-modified silicones, and fluorine-modified silicones.

[0043] The content of the oily component is usually 0.1 to 90% by mass, and preferably 4 to 40% by mass, based on the total mass of the cosmetic composition, and the content of the water is usually 10 to 99% by mass, and preferably 50 to 95% by mass, based on the total mass of the cosmetic composition.

[0044] The solid particles include low-specific-gravity solid particles having a specific gravity of less than 1 relative to the liquid component, and high-specific-gravity solid particles having a specific gravity of 1 or more relative to the liquid component. The specific gravity of the low-specific-gravity solid particles is preferably 0.01 to 0.99, and more preferably 0.20 to 0.95. The specific gravity of the high-specific-gravity solid particles is preferably 1.01 to 20, and more preferably 1.05 to 10, and even more preferably 1.05 to 1.25.

[0045] The solid particles that can be contained in the cosmetic composition may be organic solid particles or inorganic solid particles.

[0046] Examples of the organic solid particles include solid fats such as solid paraffin, ceresin, synthetic wax, and carnauba wax; polyesters such as polylactic acid, polyhydroxybutyric acid, and polyacrylic acid / acrylic acid ester; polyamides such as nylon; polyethylene, polypropylene, polyurethane, vinyl resin, tetrafluoroethylene, polymethyl methacrylate, cellulose, silk, and polymer particles such as polymethylsilsesquioxane.

[0047] Examples of the inorganic solid particles include particles of magnesium oxide, barium sulfate, calcium sulfate, magnesium sulfate, calcium carbonate, magnesium carbonate, talc, mica, kaolin, sericite, silica, aluminum silicate, magnesium silicate, aluminum magnesium silicate, calcium silicate, hydroxyapatite, zeolite, secondary calcium phosphate, alumina, aluminum hydroxide, and boron nitride. When the inorganic solid component is an ultraviolet scattering agent, examples of the agent include zinc oxide, zirconium oxide, and titanium oxide. Furthermore, when the inorganic solid component is a pigment, examples of the inorganic solid component include inorganic red pigments such as iron oxide and iron titanate, inorganic brown pigments such as γ-iron oxide, inorganic yellow pigments such as yellow iron oxide and ocher, inorganic black pigments such as black iron oxide and carbon black, inorganic purple pigments such as manganese violet and cobalt violet, inorganic green pigments such as chromium hydroxide, chromium oxide, cobalt oxide and cobalt titanate, inorganic blue pigments such as iron blue and ultramarine, white pigments such as titanium mica, pigment-coated titanium mica and titanium oxide, and pearl pigments such as synthetic phlogopite.

[0048] The content of the solid particles is usually 0.1 to 50% by mass, and preferably 0.5 to 30% by mass, based on the total mass of the cosmetic composition.

[0049] The cosmetic composition may contain a surfactant, but since the cosmetic composition contains the cation-modified diutan gum and thus has improved emulsion stability, the content of the surfactant may be less than usual. In a typical cosmetic composition, the content of the surfactant is 0.1 to 50% by mass relative to the total mass of the cosmetic composition, whereas in the cosmetic composition of the present embodiment, the content of the surfactant may be, for example, 0.1% by mass or less, or 0.01% by mass or less, or the cosmetic composition may substantially not contain the surfactant. In order to impart a function specific to the surfactant to the cosmetic composition, the content of the surfactant is preferably 10 to 40% by mass, more preferably 10 to 20% by mass.

[0050] Examples of the surfactant include cationic surfactants, anionic surfactants, nonionic surfactants, and amphoteric surfactants. From the viewpoint that the surfactant exhibits compatibility with the cation-modified diutan gum, the surfactant preferably includes any one of anionic surfactants, nonionic surfactants, and amphoteric surfactants. In addition, it is more preferable that the surfactant includes a plurality of types of these. By combining the cation-modified diutan gum and the surfactant, the cosmetic composition has further excellent dispersion stability. In addition, the cosmetic composition has a function specific to the surfactant. For example, in the case of the cleansing cosmetic composition, the composition has a function of improving hair conditioning properties and improving foam quality.

[0051] Examples of the cationic surfactant include alkyl trimethyl ammonium salts, dialkyl dimethyl ammonium salts, alkyl pyridium salts, alkyl dimethyl benzyl ammonium salts, benzethonium chloride, and benzalkonium chloride.

[0052] Examples of the anionic surfactant include alkyl (carbon number: 8 to 24) sulfates, alkyl (carbon number: 8 to 24) ether sulfates, alkyl (carbon number: 8 to 24) benzenesulfonates, alkyl (carbon number: 8 to 24) phosphates, polyoxyalkylene alkyl (carbon number: 8 to 24) ether phosphates, alkyl (carbon number: 8 to 24) sulfosuccinates, polyoxyalkylene alkyl (carbon number: 8 to 24) ether sulfosuccinates, acylated (carbon number: 8 to 24) alanine salt ... Examples of such salts include acylated N-methyl-β-alanine salts (having 8 to 24 carbon atoms), acylated glutamates (having 8 to 24 carbon atoms), acylated isethionates (having 8 to 24 carbon atoms), acylated sarcosinates (having 8 to 24 carbon atoms), acylated taurines (having 8 to 24 carbon atoms), acylated methyl taurines (having 8 to 24 carbon atoms), α-sulfofatty acid ester salts, ether carboxylates, polyoxyalkylene fatty acid monoethanolamide sulfates, and long-chain (having 8 to 24 carbon atoms) carboxylates.

[0053] Examples of the nonionic surfactant include alkanolamides, glycerin fatty acid esters, polyoxyalkylene alkyl ethers, polyoxyalkylene glycol ethers, polyoxyalkylene sorbitan fatty acid esters, sorbitan fatty acid esters, polyoxyalkylene sorbitol fatty acid esters, sorbitol fatty acid esters, polyoxyalkylene glycerin fatty acid esters, polyoxyalkylene fatty acid esters, polyoxyalkylene alkylphenyl ethers, tetrapolyoxyalkylene ethylenediamine condensates, sucrose fatty acid esters, polyoxyalkylene fatty acid amides, polyoxyalkylene glycol fatty acid esters, polyoxyalkylene castor oil derivatives, polyoxyalkylene hydrogenated castor oil derivatives, alkyl polyglycosides, and polyglycerin fatty acid esters.

[0054] Examples of the amphoteric surfactant include alkyl (C8-24) amidopropyl betaine, alkyl (C8-24) carboxybetaine, alkyl (C8-24) sulfobetaine, alkyl (C8-24) hydroxysulfobetaine, alkyl (C8-24) amidopropyl hydroxysulfobetaine, alkyl (C8-24) hydroxyphosphobetaine, alkyl (C8-24) aminocarboxylate, alkyl (C8-24) amphosodium, alkyl (C8-24) amine oxide, alkyl (C8-24) phosphate containing tertiary nitrogen and quaternary nitrogen, and the like.

[0055] Furthermore, the cosmetic composition may contain other additives, such as polyhydric alcohols that function as moisturizing agents, such as glycerin and 1,3-butylene glycol, thickeners, such as xanthan gum, antioxidants, such as tocopherol and BHT, UV absorbers, such as benzophenone derivatives, para-aminobenzoic acid derivatives and methoxycinnamic acid derivatives, chelating agents, such as edetate, amino acids, such as arginine and glutamic acid, pH adjusters, bactericides, preservatives, vitamins, anti-inflammatory agents, colorants, fragrances, and foam enhancers.

[0056] As described above, the cation-modified diutan gum according to this embodiment has A cation-modified diutan gum in which a portion of the hydroxyl groups is substituted with a quaternary nitrogen-containing group represented by chemical formula (1), The amount of cationic charge derived from the quaternary nitrogen-containing group is 0.3 to 0.8 meq / g. [ka] (R in the formula 1 and R 2 is an alkyl group having 1 to 3 carbon atoms, and R 3 is an alkyl group having 1 to 24 carbon atoms, and R 4 and R 5 is an alkyl group having 1 to 3 carbon atoms or a hydrogen atom, and X - indicates a monovalent anion)

[0057] According to this configuration, the cationic charge amount is 0.3 to 0.8 meq / g, so that the dispersion stability of the liquid composition can be improved.

[0058] In addition, the cation-modified diutan gum according to this embodiment is preferably R 4 and R 5 is a hydrogen atom.

[0059] According to this configuration, R 4 and R 5 When is a hydrogen atom, the dispersion stability of the liquid composition can be further improved.

[0060] In addition, the cation-modified diutan gum according to this embodiment is preferably R 3 is an alkyl group having 1 to 3 carbon atoms.

[0061] According to this configuration, R 3 When is an alkyl group having 1 to 3 carbon atoms, the dispersion stability of the liquid composition can be further improved.

[0062] In addition, the cation-modified diutan gum according to this embodiment is preferably R 1 , R 2 and R 3 is a methyl group.

[0063] According to this configuration, R 1 , R 2 and R 3 When is a methyl group, the dispersion stability of the liquid composition can be further improved.

[0064] The dispersion stabilizer according to the present embodiment contains the cation-modified diutan gum.

[0065] According to such a configuration, by containing the above-mentioned cation-modified diutan gum, when it is contained in a liquid composition or emulsion composition containing solid particles, it is possible to impart excellent dispersion stability to these compositions.

[0066] Moreover, the cosmetic composition according to the present embodiment contains the above-mentioned cation-modified diutan gum.

[0067] According to this configuration, by containing the cation-modified diutan gum, excellent dispersion stability is obtained.

[0068] Moreover, the cosmetic composition according to this embodiment preferably contains a surfactant, and the surfactant contains any one of an anionic surfactant, an amphoteric surfactant, or a nonionic surfactant.

[0069] According to this configuration, the surfactant contains any one of an anionic surfactant, an amphoteric surfactant, and a nonionic surfactant, thereby resulting in excellent compatibility between the surfactant and the cation-modified diutan gum.

[0070] Moreover, the cosmetic composition according to this embodiment is preferably a cleansing cosmetic composition.

[0071] According to this configuration, since the cosmetic contains the cation-modified diutan gum, when used in a cosmetic for cleansing purposes, the cosmetic has excellent quality.

[0072] As described above, one embodiment has been shown as an example, but the cation modified diutan gum according to the present invention is not limited to the configuration of the above embodiment. Moreover, the cation modified diutan gum according to the present invention is not limited by the above-mentioned action and effect. The cation modified diutan gum according to the present invention can be modified in various ways without departing from the gist of the present invention. EXAMPLES

[0073] The present invention will be further described below with reference to examples, but the present invention is not limited to these.

[0074] [Example 1] 1.55 g of sodium hydroxide was dissolved in 49.44 g of water, and 74.88 g of isopropanol was uniformly dissolved. Then, 30 g of diutan gum (KELCO-VIS DG, manufactured by CP Kelco US, Inc.) was added while being dispersed. 6.0 g of glycidyl trimethylammonium chloride (hereinafter sometimes referred to as GTA; SY-GTA80, manufactured by Sakamoto Yakuhin Kogyo Co., Ltd.) was added, and reacted at 50 to 55°C for 4 hours. After the reaction was completed, the mixture was neutralized with 1.52 g of 50% by mass sulfuric acid. The reaction product was filtered, washed by dispersing in 131.52 g of 60% isopropanol, and then filtered. Next, the reaction product was washed by dispersing in 101.76 g of 75% isopropanol, and then filtered. Furthermore, excess GTA was removed by washing by dispersing in 72 g of 90% methanol, and the desired cation-modified diutan gum was obtained after drying. The cationic charge of the resulting cationically modified diutan gum was 0.443 meq / g. The results are shown in Table 1.

[0075] [Examples 2-3 and Comparative Examples 1-2] Cation-modified diutan gums having different cationic charge amounts were produced in the same manner as in Example 1, except that the amount of GTA used for cationic modification was set to the value shown in Table 1, and the cationic charge amounts were measured.

[0076] [Comparative Example 3] The diutan gum used in Example 1 was used as Comparative Example 3, and its nitrogen content was measured.

[0077] [Table 1]

[0078] As shown in Table 1, the nitrogen content and cationic charge of the cation-modified diutan gum increased with an increase in the amount of GTA. In other words, it was found that it is possible to adjust the cationic charge of the cation-modified diutan gum by changing the amount of GTA.

[0079] [FT-IR measurement of cation-modified diutan gum] Using a Fourier transform infrared spectrophotometer (FT / IR-4600, manufactured by JASCO Corporation, ATR method), the IR spectra of Example 2 and Comparative Example 3 (unmodified diutan gum) were measured. Spectral data for comparing these are shown in FIG.

[0080] As shown in FIG. 1, the cation-modified diutan gum of Example 2 has a first peak P1 at 1730 cm compared to the unmodified diutan gum of Comparative Example 3. -1 A significant decrease in the peak intensity around 1250 cm was observed. -1 Nearby peaks and 1400cm -1 The peak intensity of the peak around 1600 cm was also decreased. -1 No significant changes were observed in the peak intensities of the nearby peaks.

[0081] In addition, the ratio of the peak intensity of the first peak P1 to the peak intensity of the second peak P2 in the IR spectrum was calculated. The peak intensity ratio was measured at the high wavenumber end of the first peak (1770 cm -1 around 1500 cm) and the low wavenumber end of the second peak ( -1 A straight line passing through the line (near the center of the peak) was used as the baseline, and the distance from the baseline to the peak top of each peak was compared. The peak intensity ratio in Example 2 was 0.20, whereas the peak intensity ratio in Comparative Example 3 was 0.73.

[0082] [Evaluation A: Evaluation of dispersion stability of solid particles] Using the cation-modified diutan gums of Examples 1 to 3 and Comparative Examples 1 and 2, and the diutan gum and cation-modified xanthan gum (Labor Gum CX, manufactured by DSP Gokyo Food & Chemical Co., Ltd.) of Comparative Example 3, aqueous solutions with a polysaccharide concentration of 0.25% by mass were prepared, and the dispersion stability was evaluated by dispersing a scrubbing agent as solid particles in the aqueous solutions. In addition, the viscosity of the 0.25% by mass aqueous solution was measured under the following measurement conditions. Specifically, 99.65 g of deionized water was placed in a 200 mL glass beaker, and 0.25 g of each polysaccharide and 0.10 g of methylparaben were added while stirring with a general-purpose stirrer (BL1200, manufactured by Shinto Scientific Co., Ltd.). Stirring was performed for 1 hour at room temperature to obtain a 0.25% by mass aqueous solution. 80 g of each 0.25% by mass aqueous solution and 4 g of a scrubbing agent (synthetic wax (organic solid particles), specific gravity 0.95, Synscrub164GRS, manufactured by Micro Powders, Inc.) were placed in a 100 mL vial, and the scrubbing agent was uniformly dispersed by shaking up and down. The obtained dispersion was placed in a 50°C incubator (MIR-153, manufactured by Sanyo Electric Co., Ltd. (now Panasonic Corporation)), and the state after standing for 24 hours was observed and evaluated according to the following evaluation criteria. The results are shown in Table 2.

[0083] (Evaluation Criteria for Dispersion Stability) Stable: The scrubbing agent does not float near the liquid surface, and no layer of scrubbing agent is visible on the liquid surface. Unstable: The scrubbing agent is floating near the liquid surface, and a layer of scrubbing agent is visible on the liquid surface.

[0084] (Viscosity measurement conditions) The 0.25% by weight aqueous solution before adding the scrubbing agent was subjected to a rheometer (DHR-2, manufactured by TA Instruments Japan, Inc.) and the flow curve was measured (temperature: 25°C) at 0.01 s -1 The viscosity at a shear rate of 1000 μg / ml was measured.

[0085] [Table 2]

[0086] As shown in Table 2, in the aqueous solutions (A-1 to A-3) containing Examples 1 to 3, the low specific gravity solid particles of the scrubbing agent did not float at all, and the dispersion state of the scrubbing agent was maintained uniformly. In contrast, in the aqueous solutions (A-4 to A-6) containing Comparative Examples 1 to 3 or the aqueous solution (A-7) containing cation-modified xanthan gum, the scrubbing agent floated, and a layer of the scrubbing agent was observed on the liquid surface. Generally, in the low shear region (0.01 s -1 ), it is considered that the higher the viscosity, the higher the dispersion stability of solid particles such as scrubbing agents. For this reason, it was speculated that the aqueous solutions containing Examples 1 to 3 had high viscosity. However, unexpectedly, the viscosity of the aqueous solutions containing Examples 1 to 3 was lower than that of the aqueous solution containing Comparative Example 3 (unmodified diutan gum), which had insufficient dispersion stability. In particular, the aqueous solution containing Example 3 had good dispersion stability, despite having a lower viscosity than any of the aqueous solutions containing Comparative Examples 1 to 3. From this, it was found that the cation-modified diutan gums of Examples 1 to 3 exhibited very excellent dispersion stability regardless of viscosity. Therefore, it was found that the cationically modified diutan gums of Examples 1 to 3 had better dispersion stability than the cationically modified xanthan gum.

[0087] [Evaluation B: Evaluation of dispersion stability of emulsion particles] Using the cation-modified diutan gums of Examples 1 to 3 and Comparative Examples 1 and 2, and the diutan gum of Comparative Example 3, emulsions with a polysaccharide concentration of 0.25% by mass and an oil component concentration of 40% by mass were prepared, and the dispersion stability of the emulsion particles was evaluated. Specifically, 100 g of deionized water was placed in a 300 mL tall glass beaker, and 0.5 g of each polysaccharide was added while stirring with a general-purpose stirrer (BL1200, manufactured by Shinto Scientific Co., Ltd.). After stirring at room temperature for 1 hour, 80 g of liquid paraffin and 0.2 g of methylparaben were added, and deionized water was further added to make a total of 200 g. After stirring at about 1000 rpm (pre-emulsification) with a general-purpose stirrer for 5 minutes, stirring (emulsification) was performed at 8000 rpm with a homogenizer (TK Robomix, stirring part: TK Homomixer MARK II 2.5 type, manufactured by Primix Corporation) for 5 minutes. The emulsion particle size (median size) of the obtained emulsion was measured (dispersion medium: water) using a laser diffraction / scattering type particle size distribution measuring device (Partica mini LA-350, manufactured by Horiba, Ltd.). The results are shown in Table 3.

[0088] [Table 3]

[0089] As shown in Table 3, in the emulsions (B-1 to B-3) containing Examples 1 to 3, the emulsion particles were less than 50 μm, and were smaller than those in the emulsions (B-4 to B-6) containing Comparative Examples 1 to 3. This shows that the cation-modified diutan gums of Examples 1 to 3 are also superior in terms of dispersion stability of emulsion particles to the cation-modified diutan gums of Comparative Examples 1 to 3. In addition, since the emulsion particles can be made smaller, it is expected that the amount of surfactant can be reduced when preparing an emulsion composition. Furthermore, since the dispersion stability is excellent, it is expected that the stability (emulsion stability) of the emulsion composition is also very high.

[0090] [Evaluation C: Evaluation of spinnability] The cation-modified diutan gums of Examples 1 to 3 and Comparative Examples 1 and 2, and the diutan gum of Comparative Example 3 were used to evaluate the spinnability of an aqueous solution with a polysaccharide concentration of 0.5% by mass. Specifically, 98.0 g of deionized water was placed in a 200 mL glass beaker, and 2.0 g of each polysaccharide was added while stirring with a general-purpose stirrer (BL1200, manufactured by Shinto Scientific Co., Ltd.). Stirring was performed at room temperature for 1 hour to obtain a 2.0 mass% aqueous solution. 12.5 g of the 2.0 mass% aqueous solution and 37.5 g of deionized water were placed in a 100 mL glass beaker, and the solution was uniformly mixed by stirring with a general-purpose stirrer at room temperature for 10 minutes to obtain a 0.5 mass% aqueous solution. 25 g of each 0.5 mass% aqueous solution was placed in a plastic dish with a diameter of 60 mm, and the plunger (diameter 8 mm) of a creep meter (RE2-33005S, manufactured by Yamaden Co., Ltd.) was brought into contact with the surface of the aqueous solution, and the plunger and the aqueous solution were separated at a speed of 5 mm / sec. The time until the solution ran out was measured. The time was calculated using the following formula, and the average value of five times was taken as the spinnability. The results are shown in Table 4. Spinnability (mm) = Time until the solution runs out (sec) x Speed ​​(5mm / sec)

[0091] [Table 4]

[0092] As shown in Table 4, the aqueous solutions containing Examples 1 to 3 (C-1 to C-3) and the aqueous solutions containing Comparative Examples 1 and 2 (C-4 to C-5) had lower spinnability than the aqueous solution containing Comparative Example 3 (C-6). Furthermore, the aqueous solutions containing Examples 1 to 3 had lower spinnability than the aqueous solution containing Comparative Examples 1 and 2. If the composition has strong stringiness, it may adhere to the sealed portion during the process of filling a container such as a tube, which may result in poor sealing or leakage. Therefore, the composition is required to break quickly without stringing during filling. In this regard, it was found that the cation-modified diutan gums of Examples 1 to 3 have low spinnability and therefore can improve the manufacturability of the products.

[0093] [Rating D: Transparency rating] In addition, a 0.5% by mass aqueous solution of cation-modified diutan gum prepared in the same manner as above and a 0.5% by mass aqueous solution of unmodified diutan gum prepared in the same manner were placed in a 1 cm long disposable cell, and the transmittance at 600 nm was measured using a spectrophotometer (U-2910, Hitachi High-Technologies Corporation). As a result, the aqueous solutions containing cation-modified diutan gum in Examples 1 to 3 had improved transmittance and good appearance with less turbidity, compared to the aqueous solution containing unmodified diutan gum in Comparative Example 3. Therefore, it was found that the cation-modified diutan gums of Examples 1 to 3 can suppress coloration of products and can be particularly suitably used in cosmetic compositions.

[0094] To summarize the above evaluation results, it was found that the cation-modified diutan gums of Examples 1 to 3 having cationic charge amounts of 0.3 to 0.8 meq / g are polysaccharides with extremely excellent dispersion stability. Therefore, it was found that the cation-modified diutan gums of Examples 1 to 3 contribute to the dispersion stability of scrubs, pigments, emulsified particles, etc. in the cosmetics field, for example, and are useful for applications such as lotions, milky lotions, beauty essences, gels, creams, facial cleansers, sunscreens, shampoos, treatments, and body soaps.

[0095] Next, the dispersion stability exhibited by cation-modified diutan gum having a cationic charge of 0.3 to 0.8 meq / g was confirmed in several cosmetic compositions.

[0096] [Evaluation E: Evaluation of dispersion stability of solid particles in scrub facial cleanser] Using the cation-modified diutan gum of Examples 1 and 3 and the cation-modified xanthan gum (Labor Gum CX, manufactured by DSP Gokyo Food & Chemical Co., Ltd.), a scrub cleanser was prepared with the composition shown in Table 5. The specific gravity of the polylactic acid (organic solid particles) used as the scrubbing agent was 1.25. Specifically, the component (1) shown in Table 5 was placed in a 30 mL glass beaker, and the component (2) was added and mixed uniformly to obtain a dispersion. The component (3) was placed in a 100 mL tall glass beaker, and the dispersion was added while stirring with a general-purpose stirrer (BL1200, manufactured by Shinto Scientific Co., Ltd.), and the beaker was then immersed in a water bath at 85 ° C. After the liquid temperature reached 80 ° C, it was stirred for 15 minutes, and a mixture of components (4) to (6) was added. Next, components (7) and (8) were added, and the mixture was cooled with water while stirring until it reached near room temperature, and component (3) was added to a total of 50 g to prepare a scrub face wash. 10 g of the obtained scrub face wash was placed in a 10 mL screw-cap test tube and left to stand in a 50 ° C incubator (MIR-153, manufactured by Sanyo Electric Co., Ltd. (now Panasonic Corporation)), and the state was observed after 3 days. The results of evaluation based on the following evaluation criteria are shown in Table 8.

[0097] (Evaluation criteria for dispersion stability of facial scrub wash) Stable: The scrubbing agent does not settle and no sedimentary layer of the scrubbing agent is observed. Unstable: The scrubbing agent settles and a sediment layer of the scrubbing agent is observed.

[0098] [Table 5]

[0099] As shown in Table 5, in scrub cleansers containing high specific gravity solid particles, the scrub cleansers containing Example 1 or Example 3 (E-1 or E-2) showed better dispersion stability than the scrub cleansers containing cation-modified xanthan gum (E-3), which is considered to have high dispersion stability.

[0100] [Evaluation F: Evaluation of dispersion stability of emulsion particles in oil-in-lotion] Oil-in lotions having the formulations shown in Table 6 were prepared using Examples 1 to 3 and Comparative Example 3, as well as cationic modified xanthan gum (Labor Gum CX, manufactured by DSP Gokyo Food & Chemical Co., Ltd.) and cationic modified guar gum (Labor Gum CG-M, manufactured by DSP Gokyo Food & Chemical Co., Ltd.). Specifically, the component (1) shown in Table 6 was placed in a 30 mL glass beaker, and then the component (2) was added and mixed uniformly to obtain a dispersion. The component (3) was placed in a 200 mL tall glass beaker, and the dispersion was added while stirring with a general-purpose stirrer (BL1200, manufactured by Shinto Scientific Co., Ltd.), and then stirred at room temperature for 30 minutes. Next, the components (4) to (6) were added in order and stirred for 5 minutes. The component (7) was added to the obtained lotion and stirred at 300 rpm for 5 minutes to prepare a total of 105 g of oil-in lotion. 80 g of the obtained oil-in lotion was transferred to a 100 mL vial and left to stand in a constant temperature incubator (MIR-153, manufactured by Sanyo Electric Co., Ltd. (now Panasonic Corporation)) at 50 ° C., and the state was observed after 6 days. The results of evaluation based on the following evaluation criteria are shown in Table 6.

[0101] (Evaluation criteria for dispersion stability of oil-in-lotion) Stable: Olive oil particles do not float or separate from the aqueous solution. Unstable: Olive oil particles rise to the surface and form a separate layer from the aqueous solution.

[0102] [Table 6]

[0103] As shown in Table 6, the oil-in lotions containing Examples 1 to 3 (F-1 to F-3) showed better dispersion stability than unmodified diutan gum (F-4), cationically modified guar gum (F-6), and oil-in lotion containing cationically modified xanthan gum (F-5), which is considered to have high dispersion stability.

[0104] [Evaluation G: Evaluation of long-term dispersion stability of solid particles and oil droplets (emulsion particles)] Aqueous solutions with a polysaccharide concentration of 0.25% by mass were prepared using the cation-modified diutan gums of Examples 1 to 3 and Comparative Examples 1 and 2, and the diutan gum of Comparative Example 3, and the dispersion stability was evaluated by dispersing a scrubbing agent (the synthetic wax (organic solid particles) used in Evaluation A) and calcium carbonate (inorganic solid particles) as solid particles, and liquid paraffin (hydrocarbon oil) as oil droplets in these solutions. Specifically, 99.65 g of deionized water was placed in a 200 mL glass beaker, and 0.25 g of each polysaccharide and 0.10 g of methylparaben were added while stirring with a general-purpose stirrer (BL1200, manufactured by Shinto Scientific Co., Ltd.). Stirring was performed for 1 hour at room temperature to obtain a 0.25 mass% aqueous solution of each polysaccharide. 8 g of each 0.25 mass% aqueous solution and 0.4 g of a scrubbing agent (synthetic wax (organic solid particles), specific gravity 0.95, Synscrub164GRS, manufactured by Micro Powders, Inc.), calcium carbonate (specific gravity 2.71, manufactured by Nacalai Tesque, Inc.), and liquid paraffin (specific gravity 0.86 to 0.89, manufactured by Nacalai Tesque, Inc.) were added to a 10 mL vial, and the beaker was shaken up and down to uniformly disperse the solid particles or oil droplets. The obtained dispersion was placed in a thermostatic chamber (MIR-153, manufactured by Sanyo Electric Co., Ltd. (currently Panasonic Corporation)) at 50° C. and allowed to stand for 90 days, after which the state was observed and evaluated according to the following evaluation criteria. The results are shown in Table 7.

[0105] (Evaluation criteria for dispersion stability of scrubbing agent) Stable: The scrubbing agent does not float near the liquid surface, and no layer of scrubbing agent is visible on the liquid surface. Unstable: The scrubbing agent is floating near the liquid surface, and a layer of scrubbing agent is visible on the liquid surface. (Evaluation criteria for dispersion stability of calcium carbonate) Stable: No calcium carbonate settles near the bottom and no layer of calcium carbonate is visible at the bottom. Unstable: Calcium carbonate has settled near the bottom and a layer of calcium carbonate is visible at the bottom. (Evaluation criteria for dispersion stability of liquid paraffin) Stable: Liquid paraffin does not float near the liquid surface, and no layer of liquid paraffin is visible on the liquid surface. Unstable: Liquid paraffin is floating near the liquid surface, and a layer of liquid paraffin is visible on the liquid surface.

[0106] [Table 7]

[0107] As shown in Table 7, in the aqueous solutions (G-1 to G-3) containing Examples 1 to 3, even after a long storage period (90 days), no floating of the low specific gravity solid particle scrubbing agent and low specific gravity oil agent was observed. In addition, no settling of the high specific gravity particle calcium carbonate was observed. In other words, the aqueous solutions (G-1 to G-3) containing Examples 1 to 3 maintained a uniformly dispersed state of the solid particles and emulsified particles for a long period of time. In contrast, in the aqueous solutions containing Comparative Examples 1 to 3 (G-4 to G-6), the scrubbing agent and liquid paraffin were observed to float, a layer of the scrubbing agent and liquid paraffin was observed on the liquid surface, or a layer of calcium carbonate formed by precipitation of calcium carbonate was observed.

[0108] [Evaluation H: Evaluation of compatibility with anionic surfactants] Compositions containing anionic surfactants were prepared using the cationically modified diutan gums of Examples 1 to 3 and Comparative Examples 1 and 2, and the diutan gum of Comparative Example 3, and the compatibility of each polysaccharide with the anionic surfactant was evaluated. In addition, the viscosity of these compositions was evaluated by the following measurement. Specifically, 29.4 g of deionized water was placed in a 100 mL glass beaker, and 0.6 g of each polysaccharide was added while stirring with a general-purpose stirrer (BL1200, manufactured by Shinto Scientific Co., Ltd.). Stirring was continued for 1 hour at room temperature to obtain an aqueous solution with a polysaccharide concentration of 2.0% by mass. 5 g of the aqueous solution was dispensed into four 15 mL conical tubes, and each conical tube was charged with sodium lauryl sulfate (alkyl sulfate having 12 carbon atoms, EMALE 0 manufactured by Kao Corporation, 10% by mass relative to the total mass of the composition), a 30% aqueous solution of sodium lauroyl sarcosine (acylated sarcosine salt having 12 carbon atoms, Sarcosinate LN-30 manufactured by Nikko Chemicals Co., Ltd., 33.4% by mass relative to the total mass of the composition), a 30% aqueous solution of sodium lauroyl methylalanine (acylated N-methyl-β-alanine salt having 12 carbon atoms), and a 20% aqueous solution of sodium lauroyl methylalanine (acylated N-methyl-β-alanine salt having 12 carbon atoms). , Alaninate LN-30 manufactured by Nikko Chemicals Co., Ltd., 33.4% by mass relative to the total mass of the composition, or a 35% aqueous solution of potassium hydroxide containing lauric acid, myristic acid, palmitic acid, and glycerin (i.e., an aqueous solution containing a long-chain carboxylate having 12 carbon atoms, a long-chain carboxylate having 14 carbon atoms, and a long-chain carboxylate having 16 carbon atoms as an anionic surfactant, Prior B-100 manufactured by Kao Corporation, 28.6% by mass relative to the total mass of the composition), and further deionized water was added to make a composition of 10 g. After mixing with a spatula, the mixture was homogenized at 10,000 rpm for 1 to 2 minutes using a homogenizer (HG-200, manufactured by Hsiangtai). The appearance of the obtained aqueous solution was observed and evaluated according to the following evaluation criteria. The results are shown in Table 8.

[0109] (Evaluation criteria for compatibility with anionic surfactants) Good compatibility: No aggregation is observed and the residual viscosity is 70% or more. Compatible: No aggregation is observed, but the residual viscosity is less than 70%. No compatibility: Aggregation is observed. (viscosity residual rate) The viscosity residual rate was calculated by the following formula.

number

[0110] [Table 8]

[0111] As shown in Table 8, when the aqueous solutions (H-1 to H-3) containing Examples 1 to 3 were mixed with the four anionic surfactants, no aggregation was observed and the viscosity was maintained. In contrast, the aqueous solution (H-4) containing Comparative Example 1 showed a large decrease in viscosity when mixed with sodium lauroylmethylalanine. The aqueous solution (H-5) containing Comparative Example 2 showed aggregation when mixed with sodium lauryl sulfate. The aqueous solution (H-6) containing Comparative Example 3 showed a decrease in viscosity when mixed with sodium lauryl sulfate, sodium lauroylsarcosine, or sodium lauroylmethylalanine, and showed aggregation when mixed with sodium lauroylsarcosine or sodium lauroylmethylalanine. These results demonstrate that the cationically modified diutan gums of Examples 1 to 3 have excellent compatibility with anionic surfactants.

[0112] Next, several cosmetic compositions were prepared using the cation-modified diutan gum of the present invention having a cationic charge of 0.3 to 0.8 meq / g, and the compatibility of the cation-modified diutan gum with surfactants and the dispersion stability of the cosmetic compositions were evaluated.

[0113] [Evaluation I: Evaluation of compatibility with surfactants and dispersion stability of solid particles in gel shampoo] A gel shampoo having the composition shown in Table 9 was prepared using the cation-modified diutan gum of Example 1 and the diutan gum of Comparative Example 3. The specific gravity of the carnauba wax (organic solid particles) used as the scrubbing agent was 0.99. Specifically, component (1) shown in Table 9 was placed in a 100 mL glass beaker, and while stirring with a general-purpose stirrer (BL1200, manufactured by Shinto Scientific Co., Ltd.), component (2) was added, followed by stirring at room temperature for 10 minutes, and then component (3) was added and stirred at room temperature for 20 minutes. Next, components (4) and (5) were added and stirred for 5 minutes. Components (6) to (8) were then added and stirred for 10 minutes to prepare a gel shampoo. The appearance of the gel shampoo obtained was observed to confirm the presence or absence of aggregation. The mixture was also subjected to a rheometer (DHR-2, manufactured by TA Instruments Japan Co., Ltd.) and measured for a flow curve (temperature: 25°C) over a period of 10 s. -1 The viscosity at a shear rate of 100 g was measured. Furthermore, 8 g of the obtained gel shampoo and 0.5 g of a scrubbing agent (carnauba wax, specific gravity 0.99, NATURESCRUB C20, manufactured by Micro Powders, Inc.) were added to a 10 mL vial, and the vial was shaken up and down to uniformly disperse the scrubbing agent in the scrub gel shampoo. The obtained scrub gel shampoo was left to stand in a thermostat (MIR-153, manufactured by Sanyo Electric Co., Ltd. (now Panasonic Corporation)) at 40°C, and the state was observed after one day. The results of evaluation based on the following evaluation criteria are shown in Table 9.

[0114] (Evaluation criteria for compatibility with surfactants in gel shampoos) Good compatibility: no aggregation observed. No compatibility: Aggregation is observed. (Evaluation criteria for dispersion stability of scrub gel shampoo) Stable: No settling or floating of the scrubbing agent is observed, and no layer of scrubbing agent is observed on the liquid surface or near the bottom. Unstable: The scrubbing agent is observed to sink or float, and a layer of scrubbing agent is observed near the surface or bottom of the liquid.

[0115] [Table 9]

[0116] As shown in Table 9, the gel shampoo (I-1) containing Example 1 showed no aggregation and a high viscosity value. In contrast, the gel shampoo (I-2) containing Comparative Example 3 caused aggregation when mixed with the components (6) to (8), and also showed a lower viscosity value than that of Example 1. These results demonstrate that the gel shampoo containing Example 1 has better compatibility with anionic surfactants and amphoteric surfactants than the gel shampoo containing Comparative Example 3. Furthermore, in scrub gel shampoos containing low specific gravity solid particles close to that of water, it was found that the scrub gel shampoo containing Example 1 (I-1) had superior dispersion stability to the scrub gel shampoo containing Comparative Example 3 (I-2).

[0117] [Evaluation J: Evaluation of compatibility with surfactants in body soap and dispersion stability of solid particles] Using the cation-modified diutan gum of Example 3 and the diutan gum of Comparative Example 3, a body soap was prepared with the composition shown in Table 10. The specific gravity of the polyhydroxybutyric acid (organic solid particles) used as the scrubbing agent was 1.25. Specifically, component (1) shown in Table 10 was placed in a 100 mL glass beaker, and while stirring with a general-purpose stirrer (BL1200, manufactured by Shinto Scientific Co., Ltd.), component (2) and component (3) were added, and the beaker was then immersed in a water bath at 83 °C. After the liquid temperature reached 80 °C, the mixture was stirred for 15 minutes, and components (4) to (7) were added and stirred for another 5 minutes. The mixture was then cooled with water until it was close to room temperature, and component (8) was added, followed by component (1) so that the total weight was 50 g, to prepare the body soap. The appearance of the obtained body soap was observed to confirm the presence or absence of aggregation. The mixture was also subjected to a rheometer (DHR-2, manufactured by TA Instruments Japan Co., Ltd.) and measured for a flow curve (temperature: 25 °C) over a period of 10 s. -1The viscosity at a shear rate of 100 g was measured. Furthermore, 8 g of the obtained body soap and 0.5 g of a scrub agent (polyhydroxybutyric acid, specific gravity 1.25, BIOSCRUB 50PC, manufactured by Micro Powders, Inc.) were added to a 10 mL vial, and the scrub agent in the scrub body soap was uniformly dispersed by shaking up and down. The obtained scrub body soap was left to stand in a thermostat (MIR-153, manufactured by Sanyo Electric Co., Ltd. (now Panasonic Corporation)) at 40°C, and the state was observed after one day. The results of evaluation based on the following evaluation criteria are shown in Table 10.

[0118] (Evaluation criteria for compatibility with surfactants in body soap) Good compatibility: no aggregation observed. No compatibility: Aggregation is observed. (Evaluation Criteria for Dispersion Stability of Scrub Body Soap) Stable: No settling of the scrubbing agent is observed and no sediment layer of the scrubbing agent is observed. Unstable: Settling of the scrubbing agent is observed and a sediment layer of the scrubbing agent is observed.

[0119] [Table 10]

[0120] As shown in Table 10, the body soap (J-1) containing Example 3 showed no aggregation and a high viscosity value. In contrast, the body soap (J-2) containing Comparative Example 3 caused aggregation when mixed with the components (4) to (7), and also showed a lower viscosity value than that of Example 3. From these results, it was found that the body soap containing Example 3 has better compatibility with anionic surfactants and nonionic surfactants than the body soap containing Comparative Example 3. In addition, it was found that, in the scrub body soaps containing high specific gravity solid particles, the scrub body soap containing Example 3 (J-1) had better dispersion stability than the scrub body soap containing Comparative Example 3 (J-2). [Explanation of symbols]

[0121] P1: 1st peak, P2: 2nd peak

Claims

1. A cation-modified diutan gum in which a part of the hydroxyl groups is substituted with a quaternary nitrogen-containing group represented by chemical formula (1), A cationically modified diutan gum having a cationic charge amount derived from the quaternary nitrogen-containing group of 0.44 to 0.7 meq / g. 【Chemistry 1】 (In the formula R 1 and R 2 is an alkyl group having 1 to 3 carbon atoms, R 3 is an alkyl group having 1 to 24 carbon atoms; R 4 and R 5 is an alkyl group having 1 to 3 carbon atoms or a hydrogen atom, and X - indicates a monovalent anion)

2. R 4 and R 5 2. The cationically modified diutan gum of claim 1, wherein is a hydrogen atom.

3. R 3 The cation modified diutan gum according to claim 1 or 2, wherein is an alkyl group having 1 to 3 carbon atoms.

4. R 1 , R 2 and R 3 4. The cationically modified diutan gum according to claim 1, wherein is a methyl group.

5. A dispersion stabilizer comprising the cation-modified diutan gum according to any one of claims 1 to 4.

6. A cosmetic composition comprising the cation-modified diutan gum according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • JP1972020635B1

  • Cation-modified polysaccharide and composition containing the same

    JP2004149573A

  • Cation-modified tragacanth gum and cosmetic composition containing the same

    JP2006321869A

  • Cationically modified agar and cosmetic composition containing the agar

    JP2006335871A

  • Cationically modified gellan gum and cosmetic composition containing the same

    JP2007009092A